Incorporation of n-3 fatty acids by the liver of mice fed linseed oil as a function of feeding duration - Perini,João Angelo Lima (2011)
The objective of this study was to evaluate the incorporation of omega-3 fatty acids (n-3 FA) on male Swiss mice livers receiving diets based on linseed oil (LO) for up to 56 days. The mice were sacrificed at 7, 14, 28, 42, 56 days and FA concentration was analyzed by gas chromatography. A total of 13 FA were identified on LO feeds presenting alpha-linolenic acid (LNA) contents of 26.97 %. A total 22 FA were identified in the livers of the mice. Part of the LNA was converted into n-3 FA (20:3n-3, eicosapentaenoic acid-EPA, 22:5n-3, and docosahexaenoic acid-DHA), and some of the LNA was stored in the liver. LNA, EPA and DHA concentrations (mg/g total lipids ) from 0 days for up 56 days increased from 1.29 to 18.90 (LNA), 0.20 to 18.90 (EPA) and 41.26 to 99.17 (DHA).The concentration of n-3 FA in the livers varied with the duration of the LO diet. During LO feed, n-6 FA concentration fell and n-3 FA concentration rose through the experimental period.